First-principles investigations of Mn doped zinc-blende ZnO based magnetic semiconductors: materials for spintronic applications - Ul Haq, Bakhtiar (Elsevier, 2015)
ZnO based magnetic semiconductors are intensively investigated because of showing strong potential as base materials for spintronic devices. In this study, full potential linearized augmented plane-wave plus local orbitals FP-L(APW+lo) scheme of computation is used to explore the structural, electronic and magnetic properties of Manganesedoped ZnO based magnetic semiconductors in zinc-blende (ZB) phase. For comprehensive understanding of Mn-doping effect on ZnO, several compositions of Mn:ZnO for 12.5%, 25%, 37.5%, 50%, 62.5%, 75% and 87.5% of Mn concentration are investigated. Our obtained results show a successful induction of the magnetic moment (MM) by Mn-doping into the ZnO matrix, without any geometrical deformation. However a marginal increase in the value of lattice constants is found up to 25% concentration of Mn for this system and for above compositions, it tends to decrease revealing the formation of secondary phases. It is also found that Mn:ZnO system favors ferromagnetic coupling for 12.5% and 25% of Mn contents that has been switched to anti-ferromagnetic coupling for higher Mn contents. The spin polarized electronic structure of Mn:ZnO system was calculated within the generalized gradient approximation (GGA). In addition, the Hubbard parameter was also employed to improve the electronic band structure calculations. The calculations performed at GGA+U level related to electronic band structures show zero energy gap for majority spin carriers, whereas a considerable energy gap is noted for minority spin carriers. This distinguished response of Mn:ZnO system to majority and minority spin carriers, in terms of resistivity and conductivity, highlights its importance for diverse applications as based material in spintronic devices like spin dependent transports, currents and other spin based electronic applications.